PENGARUH KUALITAS PELAYANAN DAN REPUTASI PERUSAHAAN TERHADAP KEPUASAN PASIEN RUMAH SAKIT IBU DAN ANAK (RSIA) ERIA BUNDA PEKANBARU - Indra S.P. Siallagan; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at , as for the purpose of this study was to determine the effect of service quality and corporate reputation to patient statisfaction at Mother and Child Hospital Eria Bunda Pekanbaru. Service quality and corporate reputation as the independent variable (X1X2) while the cost patient statisfaction as the dependent variable (Y). The problem in this research was the patient that expirience fluctuation. Seen from the presentation the list of the development of a patient in the last 5 year. The research sample was taken of 100 respondents of the population was calculated using the Slovin formula. The data was getting from the questionnaire and subsequently processed to then be tested with statistics through SPSS. From the results which shows that service quality and corporate reputation have a positive and significant impact on patient statisfaction at Mother and Child Hospital Eria Bunda Pekanbaru.Keywords: Service Quality, Corporate Reputation and patient statisfaction.